IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN INDONESIAN LANGUAGE LEARNING - Yunus, Rusyda Nazhirah; Rosida, Sisi; Ramadani, Mutiara (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Curriculum changes are a natural process in education. The introduction of a new curriculum serves to refresh, expand, and improve the current curriculum. Curriculum changes reflect the government's efforts in developing the education system. In 2022, there was another curriculum change, namely the Merdeka Curriculum. Merdeka Curriculum is a curriculum approach that prioritizes diverse content in extracurricular learning, which will provide more time for learners to understand concepts and strengthen their competencies. Teachers also have the freedom to choose various teaching aids, so that learning can be tailored to learners' learning needs and interests. Teachers' performance must be better, as they have not fully understood the Merdeka Curriculum. Based on the results of the research conducted, the implementation of the independent curriculum has been getting better and more intensive and has succeeded in making students more creative, enthusiastic, and have good character. Based on the results of the research conducted, the implementation of the independent curriculum has been getting better and more intensive and has succeeded in making students more creative, enthusiastic, and have good character